Baryon number fluctuations at finite temperature and density - Fu, Wei-jie; Pawlowski, Jan M.; Rennecke, Fabian (Arxiv, 2016)
We investigate baryon number fluctuations for finite temperature and density in two-flavor QCD. This is done within a QCD-improved low-energy effective theory in an extension of the approach put forward in [1,2]. In the present work we aim at improving the predictive power of this approach for large temperatures and density, that is, for small collision energies. This is achieved by taking into account the full frequency dependence of the quark dispersion. This ensures the necessary Silver Blaze property of finite density QCD for the first time, which so far was only implemented approximately. Moreover, we show that Polyakov loop fluctuations have a sizeable impact at large temperatures and density. The results for the kurtosis of baryon number fluctuations are compared to previous effective theory results, lattice results and recent experimental data from STAR.